PREVENTION AND TREATMENT OF INFECTIOUS COMPLICATIONS POST HSCT - Maiolino, Marcia Garnica; Carlesse, Fabianne; Ramos, Jessica Fernandes (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
THE BRAZILIAN SOCIETY FOR BLOOD AND MARROW TRANSPLANTATION (SBTMO) PRESENTS THE BRAZILIAN GUIDELINES ON HEMATOPOIETIC STEM CELL TRANSPLANTATION